Implementation of a Website-Based Student Association Activity Management Information System Using the Prototype Method - Hendra, Johanda Putra; aryani, reni; A., muhammad razi (JUSS (Jurnal Sains dan Sistem Informasi), 2026)
The management of Student Association (HIMA) activity administration at the Faculty of Science and Technology, Universitas Jambi, is still carried out manually, from activity proposal submission, proposal and budget plan (RAB) preparation, to accountability reporting (LPJ), making the process slow, difficult to monitor, and prone to document loss. This study aims to implement the prototype model in building a web-based Student Activity Management Information System (SIPEKMA) and to determine the functional test results of the system using black box testing. The development followed the prototype stages of communication, quick plan, modeling quick design, construction of prototype, and delivery and feedback, with system modeling using Unified Modeling Language (UML) in the form of activity diagrams, class diagrams, and sequence diagrams. The system was built with the Laravel framework and MySQL database and was developed through two iterations based on user feedback. Black box testing of 135 functions across four user roles (48 HIMA functions, 26 Advisor functions, 25 Head of Study Program functions, and 36 Vice Dean III functions) produced X = 100% of functions running well and Y = 0% of functions failing, so the system is considered good in terms of functionality and ready to simplify student activity administration.